Informal Caregiving in a Medically Underserved Community: Challenges, Construction of Meaning, and the Caregiver-Recipient Dyad - Rita Gorawara-Bhat PhD; Jeffrey Graupner MPH; Jason Molony AM; Katherine Thompson MD (SAGE Publishing, 2019)
Little is known about informal caregivers' challenges in medically underserved communities. This qualitative study explores their perceptions/experiences of caregiving in a medically underserved community in Midwest United States. Two focus groups ( n  = 12) were conducted and themes were extracted and analyzed. Theme 1 included perceived barriers/unmet needs; most prevalent of which were lack of informational resources and support groups. A second unsolicited and unanticipated theme highlighted how caregivers constructed meaning through reappraising challenges to create enriching experiences for themselves, reinforcing their evolving dyadic relationship with care-recipient. Challenging and enriching aspects of caregiving coexisted and were rooted in caregiver-care-recipient dyad. Caregivers used meaning-making as a coping strategy for challenges. Prior research corroborates caregivers' challenges and meaning-making; this study contributes by delineating how both become interrelated. Policy makers can (a) alleviate challenges by increasing informational resources and support groups and (b) provide training to optimize caregivers' meaning-making, thus enhancing their positive experiences.